Webinar introduction to big data - Tang, Howe Eng; Daneil, Imelia Laura; Kamaruddin, Siti Faridah (UiTM Sarawak, 2021)
Webinar Introduction to Big Data was organized by Research & Industrial Linkages Unit, Universiti Teknologi MARA Sarawak Branch, Mukah Campus on 24 September 2020 through Online Cisco Webex. The speaker is Associate Professor Dr Leong Siow Hoo, a data scientist who has more than fifteen years of experience in data processing, analyzing, and interpreting.